Miguel Hidalgo ou les récits d’une figure emblématique de l’indépendance mexicaine - Dalila Chine (Les Cahiers ALHIM)
The images of an iconic figure such as that of Miguel Hidalgo in the Mexican textbooks are an immeasurable source for any researcher interested in the role of iconography in the construction of national identity. At a time when the bells of festivities throughout the country to mark the bicentenary of independence are ringing, we return to this article on the variations of speech related to this character erected as an icon for all schoolchildren. Through the textbooks of history from 1960 to 2000, we seek to understand how the narrative of Independence is constructed through the symbol. We will also evalue the rightful place it occupies in the formation of a national consciousness. By a cathartic effect, the images and discourses on Miguel Hidalgo aim to create a paternity case, a sort of pact between the schoolboy and his community. Independence is told to children of primary school as a family history, a turbulent history with its joys and sorrows, a story which, in sum, tries to engage these future citizens by inculcating values of respect, values considered necessary for internalization of patriotism.